Reporting uncertified science in the news media during the Covid-19 pandemic - Schalkwyk, Francois, Van; Dudek, Jonathan (My University, 2022)
Preprints have gained prominence in the dissemination of scientific findings. This development has been reinforced by the Covid-19 pandemic, which continues to require the rapid dissemination of new scientific information. However, since preprints usually have not undergone peer review, they lack the rigor of other scientific publications such as journal articles. This presents a challenge for the news media tasked with keeping the public informed about the latest scientific developments in the context of great uncertainty during a global pandemic. This research note investigates the reporting of scientific information from preprints in 80 news articles identified in news articles related to Covid-19 published in four South African online media outlets. Our results show that despite the publication of guidelines for reporting on preprints in the media, there is still a way to go regarding the judicious use of scientific information from preprints by the news media.
Keywords: preprint; covid-19; uncertified science; media; South Africa; science communication; science journalism